Effect of Flat Cornea on Visual Outcome after LASIK - Engy Mohamed Mostafa (Journal of Ophthalmology)
Purpose. To evaluate the effect of preoperative and postoperative keratometry on the refractive outcome after laser in situ keratomileusis (LASIK) for moderate and high myopia. Methods. Records of 812 eyes (420 patients) with myopia ≥−6 D who had LASIK at Sohag Laser Center, Egypt, from January 2010 to November 2013, were retrospectively analyzed. Main outcome measures were postoperative corrected distance visual acuity (CDVA), postoperative spherical equivalence, and postoperative Q factor. Results. LASIK was performed in 812 eyes (mean age 21.8±5.2 years). Patients were grouped according to the degree of preoperative myopia into three groups: Group 1, −6 D to −7.9 D; Group 2, −8 to −9.9 D; and Group 3, −10 to −12 D. The refractive outcome among the different myopia groups was stratified by pre- and postoperative keratometry. A trend toward greater undercorrection was noted in eyes with preoperative keratometry <43.5 D compared with those with steeper keratometry >46 D in all myopia groups. The undercorrection was also noted in postoperative keratometry groups <35 D. Conclusions. Preoperative and postoperative keratometry appeared to influence the refractive outcome especially in high myopic eyes.